The Impact of Leadership, Creativity, and Innovation on Competitive Advantage: Proposing a Comprehensive Framework for a Better Indonesia - Hartono, Hendry (Bina Nusantara University, 2013)
This paper contributes to the existing literature by exploring the relationship of creativity, leadership, and innovation on competitive advantage; and explores the connection between creativity, leadership, and innovation. Research used literature review method as a systematic search of published works to find out what is already known about the intended research. Every company that wants to survive in the global market must have vehicles, like creativity and innovation. Beside, managing effectively to create sustainable competitive advantage needs leadership because leaders are central to the process of creating culture, systems, and structure that foster creativity and innovation.